(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
The paper booklet Brescia, Università Cattolica, Biblioteca di Storia Scienze «Carlo Viganò», E - 3, with two unknown texts on the construction and use of astrolabe (Compositio astrolabii and Modus operandi in astrolabio), shows a double dating and was copied in Bassano del Grappa between February 28th and March 8th 1457. DOI 10.17464/9788867743292